2014
DOI: 10.1002/macp.201300698
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation‐Induced Emission of Tetraphenylethylene in Styrene‐Based Polymers

Abstract: In the present work, the preparation of different styrene-based polymer films containing small amounts of TPE and the evaluation of their photoluminescent behaviour is reported. When TPE is dispersed in a poor solvent or in a glassy PS matrix, the arrested intramolecular rotations of its aryls favour the strong emission of light centred at about 455-460 nm. Conversely, TPE fluorescence significantly weakens to a faint signal when good solvents or viscous but not glassy polymer matrices are used. Near-field opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Guided by the RIM working mechanism, when AIEgens are doped into polymer matrix with different rigidities, their emission would change according to the surrounding environment. Pucci and coworkers have ingeniously applied TPE as a morphological probe for several styrene‐based polymers to distinguish the host polymer matrixes according to their different composition, architecture, and inherent viscosity as well as the intrinsic stiffness . Similarly, our group has demonstrated a simple, fast, and powerful method for high‐contrast visualization and differentiation of micrometer‐sized phase separation in polymer blends using AIEgen as dopant and probe ( Figure A) .…”
Section: Physical Doping Aiegens With Polymer Materialsmentioning
confidence: 91%
“…Guided by the RIM working mechanism, when AIEgens are doped into polymer matrix with different rigidities, their emission would change according to the surrounding environment. Pucci and coworkers have ingeniously applied TPE as a morphological probe for several styrene‐based polymers to distinguish the host polymer matrixes according to their different composition, architecture, and inherent viscosity as well as the intrinsic stiffness . Similarly, our group has demonstrated a simple, fast, and powerful method for high‐contrast visualization and differentiation of micrometer‐sized phase separation in polymer blends using AIEgen as dopant and probe ( Figure A) .…”
Section: Physical Doping Aiegens With Polymer Materialsmentioning
confidence: 91%
“…This work was initially designed to determine the phase dispersion behavior of TPE in phase-separated domains of the poly(b-styrene-b-butadiene-b-styrene) (SBS) thermoplastic elastomer [96]. It was actually found that the TPE emission at room temperature resulted as being enhanced in SBS films.…”
Section: Aie and Mechanochromic Fluorescent Polymersmentioning
confidence: 99%
“…Contrary to the “classical” behaviour of organic fluorophores, these molecules emit weakly or moderately in dilute solutions, amorphous or disordered solids but become very efficiently emissive when aggregated in concentrated solutions or in crystalline states. Over the last years, a real effort has been made to understand and optimize the luminescent properties of chromophores exhibiting AIE (AIEgens) in order to use them in high‐tech innovative devices such as light‐emitting diode (OLED) or luminescent solar concentrators (LSC) . To incorporate these luminophores into such optoelectronic devices, luminescent molecules should be in assemblies into thin films, aggregates or polymer matrix.…”
Section: Introductionmentioning
confidence: 99%